Expanding the meaning of anti-corruption education in facing the challenges of corruption eradication - Akmal, Diya Ul (Jurnal Pallangga Praja (JPP), 2024)
The development of corruption cases, which are currently occurring, is a form of failure of the prevention efforts that have been carried out. The rationalization of corruption in the social environment of society is an obstacle that has not yet been resolved. This is exacerbated by the fact that anti-corruption education has not been fully effective in shaping the character and morality of the younger generation. The aim of this study is to determine the relationship between moral values and acts of corruption. In addition, this study aims to reformulate the meaning of anti-corruption education. This is a qualitative study using a normative legal method, whose data were obtained through literature review. The study’s findings show that the ongoing cases of corruption point to a false rationalization of moral perceptions. Expanding the meaning of anti-corruption education is a first step that can be taken to solve this problem. The firmness of law enforcement against corruptors can be the best anti-corruption education. In addition, the implementation of anti-corruption education that is contextually normative must also be accompanied by the use of technology to increase the interest of the younger generation. Anti-corruption education must be aimed at creating anti-corruption rationalization in facing the challenges of corruption that occur.